Moroccan Arabic in advertising context: Analysis of oral and written messages - Abdelati, Samera (Lingua Posnaniensis, 2026)
The outputs of the contact due to the presence and interaction of multiple languages in Morocco have been tackled by numerous sociolinguistic studies over the years (Ennaji 2002, Chekayri 2006, Caubet 2017b). This research attempts to illustrate the way this complex linguistic landscape affected the language of oral and written Moroccan advertising, wherein the alternation of registers and the functional expansion of the dārija became more detectable. To this end, in this study I aim to explore the correlation between language use and target audience, after providing a general overview of the first advertising materials disseminated in Morocco since the beginning of the 20th century. The discussion on linguistic innovations in this field will be accompanied by an analysis of commercials that have been aired on 2M, Morocco’s most popular television channel, since the 1960s-70s. This focus will allow us to emphasise the peculiarities of mostly oral advertising messages based on the target audience they seem to address. Further, the second part of the paper will be devoted to the reflection on the orthographic representation strategies used by speakers of Moroccan Arabic, by means of the analysis of billboards, which represent the so-called ‘outdoor advertising’. Furthermore, such billboards, whose pictures have been captured in various parts of Morocco, provide us with an opportunity to observe contact phenomena of alternation, insertion, and code-mixing (Appel & Muysken 1987), and to evaluate their role in the effectiveness of the advertising message, as well as to provide some observations in their orthographic treatment.